2020
DOI: 10.1167/jov.20.12.9
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of choice history and evidence history resolve a paradox of sequential choice bias

Abstract: Perceptual decisions are biased toward previous decisions. Earlier research suggests that this choice repetition bias is increased after previous decisions of high confidence, as inferred from response time measures (Urai, Braun, & Donner, 2017), but also when previous decisions were based on weak sensory evidence (Akaishi, Umeda, Nagase, & Sakai, 2014). As weak sensory evidence is typically associated with low confidence, these previous findings appear conflicting. To resolve this conflict, we set out to inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 42 publications
6
62
1
Order By: Relevance
“…Although the mechanisms mediating serial dependence remain far from clear, our findings with orientation judgments point to a relatively early site of action of the priors, a site encoding raw orientation signals unaffected by spatial context. Obviously, this does not exclude the role of other factors, like attention 10,29 and confidence, [30][31][32] or processes such as short-term memory. 16,[33][34][35][36] How these interact with the early mechanisms revealed in this study remains open, subject to further research.…”
Section: Report Discussionmentioning
confidence: 99%
“…Although the mechanisms mediating serial dependence remain far from clear, our findings with orientation judgments point to a relatively early site of action of the priors, a site encoding raw orientation signals unaffected by spatial context. Obviously, this does not exclude the role of other factors, like attention 10,29 and confidence, [30][31][32] or processes such as short-term memory. 16,[33][34][35][36] How these interact with the early mechanisms revealed in this study remains open, subject to further research.…”
Section: Report Discussionmentioning
confidence: 99%
“…A positive influence of prior choices has also been documented in many studies ( Kaneko and Sakai, 2015 ; Talluri et al, 2018 ; Feigin et al, 2021b ). Furthermore, converging evidence from many recent studies suggests that the influence of prior stimuli and prior choices are often in opposite directions – that is, a negative (adaptive) influence of prior stimuli vs. a positive (consistency bias) influence of prior choices, and that these superimpose ( Fritsche et al, 2017 ; Bosch et al, 2020 ; Feigin et al, 2021b ; Sadil et al, 2021 ). However, opposing effects of prior sensory vs. prior choices on perceptual decisions has not yet been studied in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier research has found evidence for individual differences in several tasks assessing hysteresis, adaptation, or their ratio (e.g., Abrahamyan, Silva, Dakin, Carandini, & Gardner, 2016;Mattar, Carter, Zebrowitz, Thompson-Schill, & Aguirre, 2018;McGovern, Walsh, Bell, & Newell, 2017;, only a few studies have attempted to quantify both effects concurrently at the level of the individual participant, by distinguishing the effects of previous stimulus support and previous percept or response (e.g., Bosch, Fritsche, Ehinger, & de Lange, 2020;Urai, Braun, & Donner, 2017;Zhang & Alais, 2019). Moreover, in none of these studies individual differences in effects of previous stimulus and perceptual choice were the focus of study.…”
Section: Individual Differences In Hysteresis and Adaptationmentioning
confidence: 99%
“…Although almost all participants showed an attractive choice history bias and all participants showed a repulsive evidence history bias, the size of the choice history bias varied considerably across participants (cf. Supplementary Figure 2 in Bosch, Fritsche, Ehinger, & de Lange, 2020).…”
Section: Individual Differences In Hysteresis and Adaptationmentioning
confidence: 99%
See 1 more Smart Citation